Dislocation and deformation analysis of Cu-Ni thin films during Nano-indentation using molecular dynamics simulation approach. (2022) - Shinde, Anil B.; Patil, Shivanjali; Patil, Pooja; Salunkhe, Rohit; Sande, Rumana; Pawar, Sahil; Patil, Vijay
Abstract: Aim of this paper is to investigate the effect of varying the size of indenter, speed of indenter and thickness of nano-coating on hardness and dislocations. The dislocation mechanism, common neighbour analysis in Cu-Ni, is analysed by changing the distinctive parameters of indentation using molecular dynamics simulation approach. Overall indentation impact and mechanisms are studied with indentation velocity, indenter radius, and Nickel layer thickness. The embedded atom method based potential is used to describe the interaction between atoms. From the analysis it was seen that by applying varying thickness of nano-coating of nickel over a copper substrate, the hardness value increases corresponding with force as the thickness of nickel coating increases. Cu-50Ni is having more value of harness, which is 43% higher than pure Copper. The total length of dislocations for Cu-50Ni was 5% and 20% less than Copper and Cu-20Ni, respectively, determined by dislocation analysis at full load. From varying loading rate analysis, is was found that hardness value for Cu-Ni bilayer with loading rate of 1.5 Å/ps is maximum compared to other loading rates and is 7.40% and 36% more than Cu and Cu-Ni at a loading rate of 0.5 Å/ps, respectively. Then from by varying indenter radius, it was seen that the hardness value decreases with an increase in indenter radius. The hardness value of Cu-Ni with an indenter radius of 30 Å is 31% and 30% more than Cu and Cu-Ni with an indenter radius of 50 Å, respectively. The total length of dislocations for Cu-50Ni was 37% and 25% less than Cu and Cu-Ni with an indenter radius of 50 Å, which was determined by dislocation analysis at full load.